Al-Madkhol Al-Insani Li Carl Rogers Fi Ta'lim Maharah Kalam Fi Qismi Al-Lughah Al-Arabiyah Wa Adabiha Bi Jami'ah Mandailing Natal Al-Islamiyah Al-Hukumiyah - Nurainun Ritonga; Samsul Haq; Fadlan Masykura Setiadi (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2023)
An approach is needed to achieve the expected objective of learning a language. One of the relevant approaches for Maharah Kalam teaching (Arabic speaking) is the humanistic approach. The objective of this study is to know the application of humanistic theory from Carl Rogers to the Maharah kalam learning process at the University level, especially in the Mandailing Natal Islamic State University. The writer employed descriptive qualitative data collection techniques consisting of direct observation on implementing educative games and learning media during the Arabic speaking class, interview with students, and documentation. Moreover, the data analysis technique was based on Miles and Huberman’s model comprising data reduction, data display, and conclusion drawing/verification. The result of the study concluded that the humanistic approach to teaching-learning Arabic speaking by applying educative games and learning media had successfully made the teaching-learning process more fun. The educative games and learning media applied were as follows: throwing the ball question, guessing pictures, snake and ladder game, drawing paper, making something by using Origami paper, guessing a word by initial letter, introductory pen, and video applications.